Monitoring Hemodinamik Non Invasif Perioperatif - Kurniawaty, Juni; Pratomo, Bhirowo Yudo; Khoeri, Fatkhur Roofi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
In perioperative medicine, hemodynamic management aims at an optimization of perfusion pressure and oxygen delivery in order to maintain or restore adequate cellular metabolism. To optimize cardiopulmonary function, hemodynamic management triggers the administration of fluids and vasoactive agents according to predefined target values of hemodynamic variables. Besides basic hemodynamic variables (blood pressure and heart rate), include advanced hemodynamic variables such as pressure- or volume-based cardiac preload variables, dynamic cardiac preload variables, and blood flow variables (stroke volume, cardiac output). A variety of invasive, less-invasive, and non-invasive hemodynamic monitoring technologies are nowadays available to assess hemodynamic variables in the operating room or the intensive care unit.